From Complaints to Loyalty: Service Factors Influencing Passenger Satisfaction at Poncol Station - Alfin Muslikhun; Rowiyani Rowiyani; Lathifatul Aulia; Mukhlidin Mukhlidin (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This research investigates the impact of several key factors on customer satisfaction at the KAI Company, specifically for train services operating at Poncol Station in Semarang. Classified as causal research, the study focuses on identifying how variables such as electronic service quality (e-quality), complaint handling, station facilities, and punctuality contribute to improved satisfaction among passengers. The research population consists of all train users at the station, without a fixed number, while a sample of 100 respondents was selected using the Lemeshow formula. Data collection methods involved the use of structured questionnaires and interviews with passengers to gain both quantitative and qualitative insights. The data analysis revealed that 85% of customer satisfaction levels can be attributed to the four main factors mentioned: the quality of digital services, the effectiveness of complaint resolution, the availability and quality of facilities, and adherence to schedules. The remaining 15% of satisfaction is influenced by other, unexamined variables. Each of the four tested variables was found to have a statistically significant individual (partial) impact on customer satisfaction. Furthermore, the simultaneous (overall) testing confirmed that these factors collectively have a strong and meaningful effect on how passengers perceive the quality of the rail service. The findings emphasize the importance of consistently improving these specific operational areas to enhance customer experiences. In particular, maintaining service reliability, responding to customer complaints efficiently, improving digital interfaces, and upgrading station facilities can lead to greater satisfaction and potentially increase customer loyalty. The study suggests that service providers like KAI must adopt a customer-centered approach that focuses on both digital and physical aspects of the travel experience to remain competitive in the transportation industry.